Starting small: Revisiting young children's perceptions of social withdrawal in China. (15th April 2015) - Ding, Xuechen; Coplan, Robert J.; Sang, Biao; Liu, Junsheng; Pan, Tingting; Cheng, Chen
<x xml:space="preserve">Abstract</x> In this reply to the commentaries by Xinyin Chen, Charissa Cheah, Yiyuan Xu, and Dawn Watling, we further discuss the conceptual and methodological challenges that arise when attempting to study beliefs about social withdrawal (1) in the unique cultural context of China and (2) in the unique developmental age period of early childhood.